Long‐Term‐Stable Strong Second Harmonic Generation in Flexible DAST−PVDF Composite Films Realized by the Interface Interactions (Adv. Mater. Interfaces 17/2021). Issue 17 (12th September 2021) - Cheng, Xiaomeng; Xu, Xiangdong; Zhang, Mingang; Gu, Yu; Wang, Ququan; Qiu, Yunhang; Fan, Ting; Jiang, Yadong; Xu, Jimmy
Abstract : DAST–PVDF Composite Films In article number 2100485, Xiaomeng Cheng, Xiangdong Xu, and co‐workers demonstrate that the interface interactions of the electrostatic interactions and the intermolecular hydrogen bonds between 4‐ N, N ‐dimethylamino‐4′‐ N ′‐methyl‐stilbazolium tosylate (DAST) and polyvinylidene fluoride (PVDF) improve the conjugation of p electrons and molecular ordering of DAST, thus making tunable and long‐term‐stable strong nonlinear optical properties of flexible composite films.